A first-principle study on photoelectric characteristics of Ce-doped ZnO. Issue 1 (1st April 2021) - Feng, Yue; Chen, Jiaojiao; Liu, Chi; Wang, Tao; Liu, Hongchen; Shen, Tao
Abstract: The influence of Ce on the properties of ZnO was elaborately investigated based on first-principles. The doping structures were set to: Zn0.9687 Ce0.0313 O, Zn0.9583 Ce0.0417 O, Zn0.9375 Ce0.0625 O, and their property changes were compared to pure ZnO. The corresponding bandgaps are 2.444 eV, 2.529 eV and 2.571 eV, respectively. The peak value of the imaginary part of the dielectric function presents a trend of gradual increase. The optical absorption edge of Ce-doped ZnO has a clear red-shift to a lower energy region. The peaks of energy loss function are much lower, indicating that the introduction of Ce reduces the excitation energy of the plasma.